Light at the end of a tunnel: An appraisal of online teaching and learning in and post COVID-19 era - Moyo, R. (South African Journal of Higher Education, 2023)
The COVID-19 pandemic was like a magic bullet in pronouncing the fourth education revolution, a period of swift migration to online teaching and learning (T&L) platforms. This became evident at the dawn of lockdown periods from March 2020, when countries all over the globe shut down businesses to contain the virus. The shutdown impacted economies negatively. Thus, the educational sector, particularly higher education, was hard hit as the shift from physical to online distance T&L exposed the wide digital divide in both developed and developing worlds. The challenges have been widely recorded, and although these seem to be clouding the opportunities that are yet to be synthesised, it is worthy of corroborating the noted opportunities to prepare for T&L trajectories. Thus, the current study is an appraisal of online teaching and learning, by critically reviewing related literature from various sources dating to the dawn of migration to distance and online T&L platforms across the globe in 2020. The objective is to identify some themes for opportunities for curriculum development brought about by the unprecedented migration to online T&L, to more effectively model current and future scenarios. The major findings, which are explanatory, indicate that online T&L increases access to education by trumping physical and geographical boundaries. Multimedia T&L formats can cater for various capabilities and learning styles. Online T&L has further prompted some education institutions to invest more in information and communication technologies (ICT) thus aligning with the fourth industrial revolution and in some cases the fifth industrial revolution. The COVID-19 era has created opportunities for the adoption of online T&L technologies among both educators and learners to align themselves accordingly. This historical epoch has significantly prompted more commitment to collaboration, partnerships, and associations in the whole education sector to solicit more resources. It is rational to conclude that the fourth industrial revolution (4IR) is manifesting itself across the globe, with some developed parts already in the fifth industrial revolution, despite the challenges and albeit at different levels. A conceptual model of a general fourth education revolution, that education institutions, particularly in the developing world, can adapt and adjust to suit their specific circumstances, has thus been developed. The model aims to improve preparation for online education instruction, which has striven, and an unknown future.